Demographic Profiles and Risk Perception of Motorcycle Riders Commuting to Work in Pulau Pinang, Malaysia - Khan, Ambareen; Surienty, Lilis; Kunitomo Asano, (Recent Trends in Civil Engineering and Built Environment, 2025)
This research aims to determine the demographic characteristics of motorcycle riders who use their motorcycles to commute to work. The survey was disseminated to 776 individuals employed by Boon Siew Honda in Batu Kawan, in the Penang State of Malaysia, and collected over time. The survey indicates a higher proportion of male employees who commute to work using motorcycles than females. Employees aged 25 to 34 preferred to commute using their motorcycles. The majority of personnel have over 20 years of riding experience. The riders commute for at least 1 to 2 hours each day for work. The demographic profile of employees working in Penang state in Malaysia is first to be examined. This analysis will provide valuable information about the demographic profiles of company employees, which can be used to improve transport planning in the future.